Find the value of `sin^2(10) + sin^2(20) + sin^2(30) + … + sin^2(80)`.
Given: - \(x^4 + \frac{1}{x^4} = 322\) and \(x > 1\). 1. We know that \((a + b)^2 = a^2 + b^2 + 2ab\). Therefore, \((a + b)^2 - 2ab = a^2 + b^2\). 2. Applying this to \(x^2 + \frac{1}{x^2}\): \[ \left(x^2 + \frac{1}{x^2}\right)^2 - 2 \times x^2 \times \frac{1}{x^2} = x^4 + \frac{1}{x^4} \] \[ \leRead more
Given:
– \(x^4 + \frac{1}{x^4} = 322\) and \(x > 1\).
1. We know that \((a + b)^2 = a^2 + b^2 + 2ab\). Therefore, \((a + b)^2 – 2ab = a^2 + b^2\).
2. Applying this to \(x^2 + \frac{1}{x^2}\):
\[ \left(x^2 + \frac{1}{x^2}\right)^2 – 2 \times x^2 \times \frac{1}{x^2} = x^4 + \frac{1}{x^4} \]
\[ \left(x^2 + \frac{1}{x^2}\right)^2 = 322 + 2 \]
\[ \left(x^2 + \frac{1}{x^2}\right)^2 = 324 \]
\[ x^2 + \frac{1}{x^2} = \pm 18 \]
Since \(x > 1\), we take the positive root:
\[ x^2 + \frac{1}{x^2} = 18 \]
3. Similarly, for \(x^3 – \frac{1}{x^3}\), we use the identity \((a – b)^2 + 2ab = a^2 + b^2\):
\[ \left(x^2 – \frac{1}{x^2}\right)^2 + 2 = 18 \]
\[ \left(x^2 – \frac{1}{x^2}\right)^2 = 16 \]
\[ x^2 – \frac{1}{x^2} = \pm 4 \]
Since \(x > 1\), we take the positive root:
\[ x^2 – \frac{1}{x^2} = 4 \]
4. Now, cubing both sides:
\[ \left(x^3 – \frac{1}{x^3}\right) – 3 \times x \times \frac{1}{x} \left(x^2 – \frac{1}{x^2}\right) = 64 \]
\[ x^3 – \frac{1}{x^3} – 3 \times 4 = 64 \]
\[ x^3 – \frac{1}{x^3} = 64 + 12 \]
\[ x^3 – \frac{1}{x^3} = 76 \]
Conclusion:
The value of \(x^3 – \frac{1}{x^3}\) is 76.
Given: - We need to find the value of \(\sin^2 10 + \sin^2 20 + \sin^2 30 + \ldots + \sin^2 80\). 1. We can pair the terms such that the sum of angles in each pair is \(90^\circ\): \(\sin^2 10 + \sin^2 80, \sin^2 20 + \sin^2 70, \sin^2 30 + \sin^2 60, \sin^2 40 + \sin^2 50\) 2. Using the identity \(Read more
Given:
– We need to find the value of \(\sin^2 10 + \sin^2 20 + \sin^2 30 + \ldots + \sin^2 80\).
1. We can pair the terms such that the sum of angles in each pair is \(90^\circ\):
\(\sin^2 10 + \sin^2 80, \sin^2 20 + \sin^2 70, \sin^2 30 + \sin^2 60, \sin^2 40 + \sin^2 50\)
2. Using the identity \(\sin^2 x + \sin^2 (90 – x) = 1\):
\(\sin^2 10 + \sin^2 80 = 1\)
\(\sin^2 20 + \sin^2 70 = 1\)
\(\sin^2 30 + \sin^2 60 = 1\)
\(\sin^2 40 + \sin^2 50 = 1\)
3. Adding these equations:
\(\sin^2 10 + \sin^2 20 + \sin^2 30 + \sin^2 40 + \sin^2 50 + \sin^2 60 + \sin^2 70 + \sin^2 80 = 4\)
Conclusion:
See lessThe value of \(\sin^2 10 + \sin^2 20 + \sin^2 30 + \ldots + \sin^2 80\) is 4.